Danantara dan Reformasi Akuntabilitas Aset Negara: Tinjauan Literatur atas Praktik Sovereign Wealth Fund dalam Konteks Akuntansi Sektor Publik - Nugroho Cahyono, Ari; Meilandri, Detti; Islamiyati, Dian; Rifanda Putri, Nia (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
The establishment of Danantara, Indonesia’s sovereign wealth fund (SWF), reflects the government’s commitment to enhancing fiscal accountability through more professional and value-oriented public asset management. This article presents a literature review on the role of SWFs within the broader framework of public finance reform, emphasizing the governance of state-owned assets as an integral part of public sector accounting systems. Using a systematic literature review approach, this study explores how Danantara can function as an instrument for identifying, recording, measuring, and disclosing state assets in a more transparent manner, in line with accrual-based standards such as SAP (Government Accounting Standards) and IPSAS (International Public Sector Accounting Standards). The findings suggest that Danantara has the strategic potential to bridge the gap between asset ownership and productive utilization, while simultaneously strengthening the government’s capacity to produce more informative and credible financial statements. Within the context of fiscal reform, Danantara is not merely an investment tool, but also a long-term strategy for advancing good governance, fiscal transparency, and sustainable asset management.